2017
DOI: 10.1590/1806-90882017000300004
|View full text |Cite
|
Sign up to set email alerts
|

USE OF RESIDUES OF FORESTRY EXPLORATION OF Pinus taeda FOR PARTICLEBOARD MANUFACTURE

Abstract: -This study aimed to evaluate the quality of particleboards manufactured with forest exploitation waste from Pinus taeda. The material in the form of branches, tree tops, stumps and roots, was obtained from a forest plantation located in the Municipality of Mafra -SC. All the material was processed into wood chips for biomass and transported to the place of studies. The Pinus industrial particles were used as control and mixed with the waste in different proportions. The experimental plan consisted of the pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Therefore, there is a growing need for the reuse of this waste wood. While most of the studies have been using these wood residues for manufacturing wood-related products [14,15], their potential as inducers for laccase production should be investigated.…”
mentioning
confidence: 99%
“…Therefore, there is a growing need for the reuse of this waste wood. While most of the studies have been using these wood residues for manufacturing wood-related products [14,15], their potential as inducers for laccase production should be investigated.…”
mentioning
confidence: 99%
“…The values of 3.14% of total extracts, 27.67% of lignin and 4.56 of pH obtained by Iwakiri et al (2017) and Pereira et al (2017) for Pinus spp. industrial particles are close to the average values found for Populus deltoides woods, demonstrating the potential of the species under study as a raw material for the particleboards production.…”
Section: Wood Propertiesmentioning
confidence: 87%
“…The expansion of wood panel industries significantly increases the demand for raw materials, forcing the search for other ones. An alternative way found by several national and international researchers is the use of residual lignocellulosic materials from planted forests and agroindustry (ALVES et al, 2014;CASTRO et al, 2014;DINHANE et al, 2015;IWAKIRI et al, 2017;MACEDO et al, 2015;TRIANOSKI et al, 2015;WEBER;.…”
Section: Introductionmentioning
confidence: 99%